Reimagining the Dutch Borderlands: State Formation in Eighteenth-Century Europe, 1713-1763. - Kop, Kasper Jan (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
Attaching workable definitions to modern statehood and exploring the manners in which modern states developed have been key areas of debate within the historiography of the early modern period. While the discussion has shifted from grand claims of ambitious centralising projects by absolute rulers to more nuanced approaches involving the practical ambitions and means of both rulers and the ruled, many avenues for the analysis of state formation remain open to exploration. Among these, the impact of borderland governance on the centralisation of authority has gained considerable traction in recent historiography. As territories at the fringe of a state's territorial jurisdiction and in close proximity to neighbouring states, the exertion of central authority in early modern borderlands frequently proved challenging, especially since local society could abuse the border forming the frontier zone to its own benefit. Here, then, along the border defining the state's territorial authority, the institutions of the state faced the greatest challenges to their rule, encountering ambitions and interests of local communities and elites that did not always align with their own, while also coming into contact with the influence of neighbouring borderland and state actors. Within the growing literature on borderland governance, the Dutch Republic's southern frontier territories, the Generaliteitslanden, have remained largely overlooked, even though these regions posed considerable and particularly varied challenges to the central government in The Hague. What made these territories stand out in particular, was the fact that within the confederated political structure of the Republic - in which the seven united provinces enjoyed considerable autonomy and wielded sovereign authority - the Generaliteitslanden formed the only European holdings of the Dutch state governed directly by its central government. As such, they provide a unique opportunity to study the centralisation of authority within a political entity that was otherwise particularly resistant to such tendencies. This thesis provides a new perspective to the historiography of the Generaliteitslanden, which to date has remained a collection of local and regional studies, by studying the nature of their governance as a whole. Specifically, it discusses trends in the approaches adopted by those wielding power in The Hague towards the most serious crises and complexities challenging their governance of the Generaliteitslanden to determine what their place was within the Republic's political structure and what impact their administration had on the centralisation of power in the institutions of the state. In doing so, it relies on the primary source material contained in the Fagel family's archives and archival supplement. Seeing five of its members serve consecutively, between 1670 and 1795, as griffiers (greffiers) of the Staten-Generaal (States-General), the Fagels formed the key conduit of information between the main body of the central government and the outside world, while also having unprecedented access to information through the management of the Staten-Generaal's archives. The Fagel griffiers were best situated to advise on complex and sensitive matters that required a centralised approach in an administrative environment marked by negotiation and compromise, and as such, their archives focus extensively on extraordinary events troubling borderland governance while omitting most mentions of everyday matters. These archives therefore allow for particularly focused analysis of a relatively broad matter in a field where a broad analysis is notably lacking.
APPROVED
Keywords: Dutch Republic; borderland governance; state formation; Generality Lands; Fagel